Of bison and man : from the annals of a bison yesterday to a refreshing outcome from human involvement with America's most valiant of beasts - Danz, Harold P. (University Press of Colorado, 1997)
"In Of Bison and Man, Harold Danz, longtime National Park Service employee and former executive director of the American Bison Association, gives a clear, informative, and highly entertaining overview of this magnificent animal. Danz explores the bison's prehistory and natural history, its complex relationship with Native Americans, the bison slaughter and recovery, the establishment of the bison as an industry, and the role bison play today, both as a food source and as a wild animal."--Jacket.